Selective targeting of B-MYB G-quadruplex using fluorescent probes - Lourenço, Pedro Afonso Amaro (2023)
Proto-oncogenes are essential genes in cells that, when altered, become oncogenes and can contribute to cancer development. An example is B-MYB, which regulates cell growth and survival and is often abnormal in cancers like lung cancer. Studying B-MYB is challenging because it has proven difficult to target with drugs. These proto-oncogenes contain DNA sequences with therapeutic potential called Gquadruplexes (G4s). These structures play roles in genetic regulation and can be targets for cancer treatment. Commonly, G4 visualization involves the use of specific antibodies or small fluorescent molecules like acridine derivatives as probes. However, these methods have limitations as they impact all G4s, making it challenging to grasp the distinct functions of each one. In this study, a specific G4 within the B-MYB gene was investigated. To do this, a probe was designed to identify it, combining an acridine derivative ligand with a DNA segment complementary to the target sequence, capable of hybridizing with the sequence adjacent to the G4 under study. This probe allowed us to study this G4 formed in the promoter region of the B-MYB oncogene. The results provided by biophysical studies showed that the ligands effectively stabilized the target G4 structure, have a moderate affinity towards it, induced a change in its topology, and have increased fluorescence in its presence. Biophysical studies of the full target (G4+ oligonucleotide tail) were also performed, and the presence of the oligonucleotide did not hinder G4 formation. The probe synthesis was successfully achieved as well as its quantification. Cellular studies demonstrated strong colocalization between the target sequence and the developed probe.